2015
DOI: 10.1093/cid/civ072
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Species: Taxonomic Complexity and Controversial Susceptibilities

Abstract: The genus Lactobacillus is a taxonomically complex and is composed of over 170 species that cannot be easily differentiated phenotypically and often require molecular identification. Although they are part of the normal human gastrointestinal and vaginal flora, they can also be occasional human pathogens. They are extensively used in a variety of commercial products including probiotics. Their antimicrobial susceptibilities are poorly defined in part because of their taxonomic complexity and are compounded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(192 citation statements)
references
References 41 publications
5
178
1
8
Order By: Relevance
“…Although Lactobacilli have a long history of safe use as microbial adjunct nutrition, their safety evaluation should not be neglected, as resistant strains may become the source for the spread of antibiotic resistance genes. Resistance to streptomycin and vancomycin was expected and also reported by several studies including Goldstein et al ., and Solieri et al . Fortunately, none of the strains in our study was resistant to chloramphenicol and tetracycline while their corresponding transferable resistant genes among lactobacilli are emerging …”
Section: Resultssupporting
confidence: 86%
“…Although Lactobacilli have a long history of safe use as microbial adjunct nutrition, their safety evaluation should not be neglected, as resistant strains may become the source for the spread of antibiotic resistance genes. Resistance to streptomycin and vancomycin was expected and also reported by several studies including Goldstein et al ., and Solieri et al . Fortunately, none of the strains in our study was resistant to chloramphenicol and tetracycline while their corresponding transferable resistant genes among lactobacilli are emerging …”
Section: Resultssupporting
confidence: 86%
“…Our results are in concurrence with other reports, where lactobacilli displayed susceptibility to nitrofurantoin (Bouridane et al, 2016). Similar to this study, Goldstein et al, (2015) also reported sensitivity of lactobacilli towards tigecycline and chloramphenicol. In contrary to our results, Bhuiyan et al, (2017) documented resistance pattern of goat milk lactobacilli towards tetracycline.…”
Section: Resultssupporting
confidence: 93%
“…92 Most lactobacilli are sensitive to erythromycin, penicillins, clindamycin and vancomycin and resistant to metronidazole and aminoglycosides, with the most notable exception that many L. rhamnosus strains are resistant to vancomycin. 93,94 …”
Section: Mechanisms Of Actionmentioning
confidence: 99%